Meat Production and Supply Chain Under COVID-19 Scenario: Current Trends and Future Prospects - Ijaz, Muawuz; Yar, Muhammad Kashif; Badar, Iftikhar Hussain; Ali, Sher; Islam, Md. Shafiqul; Jaspal, Muhammad Hayat; Hayat, Zafar; Sardar, Aneeqa; Ullah, Sana; Guevara-Ruiz, Denise (Frontiers in Veterinary Science, 2021)
The COVID-19 pandemic impacted meat production, supply chain, and meat prices that caused a severe socio-economic crisis worldwide. Initially, meat and meat products' prices increased due to less production and increased demand, mainly due to panic buying. Whereas later on, both meat production and demand were significantly decreased due to lockdown restrictions and lower purchasing power resulting in a decrease in meat prices. In early April 2020, meat packing facilities started to shut down due to the rapid spread of the COVID-19 virus among workers. Due to lockdown restrictions, lower availability of a labor force, and local and international exportation legislation changes, producers developed difficulty harvesting and shipping their products. This significantly impacted the meat industry as there was a decrease in meat facilities' production, processing, and distribution capacity. Therefore, this review aimed to discuss the different aspects of the meat industry and supply chain during the COVID-19 pandemic. It is suggested that the integration among all the meat industry stakeholders is quite essential for the sustainability of the industry's supply chain of controlled prices to cope with any other devasting conditions the future may hold.